Left ventricular mass, geometry, and filling in endurance athletes: association with exercise blood pressure - Karjalainen, J.; Mantysaari, M.; Viitasalo, M.; Kujala, U. (Journal of Applied Physiology, 1997)
We studied whether left ventricular (LV) mass and concentricity [relative myocardial volume (RMV)] are associated with exercise blood pressure (BP) in athletes. LV structure and filling were evaluated by Doppler echocardiography and BP in maximal bicycle ergometry and isometric handgrip tests on 32 male endurance athletes and 15 age-matched controls. Indexed LV mass was 145 +/- 14 (SD) g/m in athletes and 93 +/- 20 g/m in controls. Mass was not associated with BP at rest or in low-grade exercise, but with heavier exercise loads this association strengthened in athletes, being maximal at peak exercise (r = 0.65 for mass and 0.58 for indexed mass; P < 0.001). Multivariate analysis indicated that BP at peak exercise accounted for 34% and the amount of training for an additional 11% of the variance in indexed LV mass. RMV was 21% larger in athletes. Only the increase in systolic BP during handgrip explained significantly (19%) the variance in RMV. LV filling velocities were not associated with mass, RMV, or BP. We conclude that in endurance athletes LV mass is associated with BP in heavy dynamic exercise and LV concentricity with BP response in static exercise.